Development of a new yarn supply for weft knitting machines to produce innovative knitwear - Prisca Holderied; Thomas Mutschler; Solveig Tresp; Julia Klausmann; Lisa Streitenberger; Marie-Ange Bueno; Marcus O. Weber (Communications in Development and Assembling of Textile Products)
The increasing demand for technical textiles makes innovations and acceleration of processes necessary. This research paper presents an innovative knitting technology. The technology, which was funded by the European Regional Development Fund as an R&D-project (EFRE-0400310), reduces production time and creates completely novel innovative knitting structures. This paper introduces the validation process of the innovative technology and therefore brings the theoretical considerations into a practical application. The yarn supply technology enables the production of an innovative double-layered fabric on flat and circular knitting machines. This double-faced fabric consists of two single-faced fabric sides which are knitted by a first yarn in the front needle bed and a second yarn in the rear needle bed. These two fabrics are joined by a third yarn knitting in both needle beds in the same carriage stroke. The method ensures that up to three yarns knit in one system pass. Furthermore, a fourth yarn can be implemented to insert a weft yarn. Additionally, the two single-faced fabrics can be produced simultaneously in the same carriage stroke in the front and rear needle beds. In this case, fewer carriage strokes are required for knitting standard structures such as Milano Rib. This structure can be produced one third faster than with conventional methods. The results show that the technology on the circular knitting machine produces good quality knitted fabrics. On the flat knitting machine, however, further research and development are needed to validate the technology.